Solid-State Modification Strategies for Alpha-Mangostin Solubility Enhancement: A Review on Recent Progress - Nurin Syamimi Ahmad Izuren Shah; Muhammad Taher Bakhtiar; Syarifah Abd Rahim; Fatmawati Adam; Wan Hazman Danial; Mohd Rushdi Abu Bakar (Journal of Pharmacy)
Introduction: Enhancing the therapeutic efficacy of active pharmaceutical ingredients requires addressing the persistent challenge of improving their solubility. Alpha-mangostin (AM), a promising natural compound with various pharmacological properties, faces significant limitations due to its low aqueous solubility. This review focuses on evaluating solid-state modification (SSM) techniques developed to enhance AM solubility. It aims to identify the most effective SSM approaches, analyse their advantages, and provide insights for future research directions in addressing solubility challenges for poorly water-soluble compounds. Methods: This review article is based on a comprehensive analysis of the literature from databases like Scopus, Google Scholar, ScienceDirect, Springer, and PubChem, covering studies published in the past 15 years. Keywords such as "solubility," "alpha-mangostin," and "solubility improvement" were utilised, with a focus on scientific articles and reviews. Results: Several strategies, such as nanoparticle technology, particle size reduction, amorphous formation, and solid dispersion, have been used to enhance AM solubility. Solid dispersion with polyvinylpyrrolidone achieved the highest solubility (2743 ?g/mL), while the AM-chitosan-oleic acid complex using nanotechnology improved AM solubility to 160 ?g/mL, an 800-fold increase from 0.2 ?g/mL. Conclusion: The reviewed methods have significantly enhanced the aqueous solubility of AM, with solid dispersion and nanotechnology showing the most promising results. These findings highlight the potential of solubility enhancement strategies to optimise AM’s pharmaceutical applications and provide a framework for improving the bioavailability of other poorly water-soluble compounds. Future research should explore alternative methods, such as co-crystallisation and advanced nanotechnologies, to further enhance solubility and formulation efficiency.